Legal Protection For Copyright Holders For Violations In The Form of Piracy of Film Cinematographic Works on The Telegram Application - Oka Sugiadnyana, I Made; Bagus Suryawan, I Gusti (Journal of Law, Politic and Humanities, 2024)
The purpose of this research is to determine the legal protection sought by cinematography copyright holders against piracy of film works via Telegram. The method used in this research is a normative legal research method with a statutory regulatory approach. The research results show that acts of piracy, such as duplicating and distributing cinematographic works without the author's permission, are legal violations that harm copyright holders, both economically and morally. In the context of legal protection for the copyright of cinematographic works, there are two forms, namely preventive legal protection by the government in the form of laws and regulations that regulate it and repressive protection through dispute resolution. Creators or copyright holders can take legal steps, either through litigation in court or non-litigation outside of court with the help of third parties, as an effort to overcome piracy of cinematographic works that occurs in the Telegram application.